RESEARCH ON THE ENERGY HARVESTING OF DIELECTRIC ELECTROACTIVE POLYMER TRANSDUCER - ZHU YinLong; XI Shuang; SU XiaoFang; LIU Ying; WANG HuaMing (Jixie qiangdu)
As a new smart material,dielectric electroactive polymer can be used to transforming mechanical energy such as wind power and water power into electrical energy. The energy harvesting mechanisms and working cycles of DEAP transducer were investigated. Three different cycles including constant charges,constant electrical voltage and constant electrical field were compared. Based on the working cycles,the energy conversion between mechanical energy inputted and electrical energy generated have been studied. With the proposed model of DEAP transducer,the force-stroke of generator in the stretching process with voltage on and the retracting process with voltage off were determined. With the force-stroke of generator,the energy generated and energy conversion efficiency were calculated. It is demonstrated that the stretch displacement and bias voltage are the main factors influencing the amount of electrical energy generated and the efficiency of energy conversion. In addition,the theoretical analysis results were validated by the experiments.